A study of clinical evaluation and management of inguinoscrotal swelling in paediatric age group - Koranga, Himadra; Chandrasekaran, R. (International Surgery Journal, 2018)
Background: Inguino-scrotal swellings are one of the commonest problems in infancy and childhood throughout the world. They represent the conditions most frequently requiring surgical repair in the paediatric age group. In many of these cases, clinical examination may sufﬁce to obtain a deﬁnite diagnosis, but when the diagnosis is inconclusive, ultrasonography can play an important role. Post-operative complications are usually rare following elective operation whereas minor complications do occur after emergency operation. In this study we evaluated various presentations of inguino-scrotal swellings, their management and complications in paediatric age group. Methods: This is a hospital based prospective study, to have an overview of a spectrum of the paediatric cases admitted in the department of surgery with inguino-scrotal swelling that includes 40 patients with age below 13 years, irrespective of sex. Data regarding clinical features, birth history, immunization, family history various blood and radiological investigations was noted. Incidences of associated anomalies, complications and any form of treatment given to the patient were recorded and findings were analysed. Results: Out of 40 cases, all were males with maximum number of cases between the age group of 3-4 years.24 cases were right sided, 12 left sided and 4 bilateral. Hydrocele was associated with 10 of the cases, undescended testis with 2 cases and 1 had encysted hydrocele of the cord. There were no complicated cases like incarceration, obstruction or strangulation. Post-operative complications were noted in 4 cases, out of which 2 were wound haematoma and one case each of wound infection and stitch granuloma. Conclusions: Childhood inguinal hernias are more common on right side due to delay in descent of right testis and males are more commonly affected. Congenital hydrocele may involutes spontaneously, so we should observed at least upto 1 year of age before considering repair but not in the case of congenital inguinal hernia. Inguinal herniotomy in children is a safe and effective operation.